PENGARUH MODEL PEMBELAJARAN TEAM GAME TOURNAMENT (TGT) TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI NILAI MUTLAK - Hajar, Tasriqah Siti; Yusmin, Edy; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to find out the effect of the Teams Game Tournament (TGT) learning model on student activities and learning outcomes on Absolute Value study material in class X of MAS Rahmatan Lil Alamin. The research method used in this study is a quantitative method with a type of research that uses a quasi-experimental form. The research design used is the Non-Equivalent Control Group Pretest-Posttest. The techniques used are observation techniques and measurement techniques in the form of tests to observe student learning outcomes with data collection tools including student activity observation sheets and student learning outcome tests. The results of the calculation of student learning activities in the classroom categorize those that are given the treatment as "Active" while those that are not given the treatment only reach the average student activity into the category "Quite Active." Before conducting hypothesis testing on student learning outcomes, the researcher implemented the data requirement testing first, including: normality testing using shapiro-wilk test and homogeneity testing. Hypothesis testing using the t-test. Based on the data obtained, it can be concluded that the Teams Game Tournament learning model has an effect on student activities and learning outcomes on the Absolute Value study material.